DNA barcoding of marine clupeid fishes (Order- Clupeiformes) of Bangladesh - Haque, Afroza Kaonine (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2019.